2018
DOI: 10.1186/s13012-018-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

Are healthcare professionals delivering opportunistic behaviour change interventions? A multi-professional survey of engagement with public health policy

Abstract: Background“Making Every Contact Count” (MECC), a public health policy in the UK, compels healthcare professionals to deliver opportunistic health behaviour change interventions to patients during routine medical consultations. Professionals’ awareness of, and engagement with, the policy is unclear. This study examined (1) awareness of the MECC policy, and (2) the prevalence of MECC-related practice in relation to (a) perceived patient benefit, (b) how often healthcare professionals deliver interventions during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 33 publications
4
96
0
Order By: Relevance
“…11,13 In the same UK survey, providing behavior change interventions took 35.3% of the appointment time. 24 However, the women in our study considered the FIGO Nutrition Checklist to be a quick intervention that is appropriate for use within a typical antenatal appointment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11,13 In the same UK survey, providing behavior change interventions took 35.3% of the appointment time. 24 However, the women in our study considered the FIGO Nutrition Checklist to be a quick intervention that is appropriate for use within a typical antenatal appointment.…”
Section: Discussionmentioning
confidence: 95%
“…In a national survey in the UK completed in 2017, 50% of healthcare professionals said that they did not provide patients with opportunistic behavior change techniques even though they perceived there was a need to do so. 24 Other barriers such as lack of time, competing priorities during pregnancy assessments, and lack of training and resources have been reported by healthcare professionals. 11,13 In the same UK survey, providing behavior change interventions took 35.3% of the appointment time.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was heterogeneous, and we sought to explore a wide range of views from diverse professional groups working in different medical professions (Dicicco‐Bloom & Crabtree, ). Participants, initially recruited through a survey panel company (YouGov), had previously taken part in a large‐scale cross‐sectional survey examining the prevalence of, and extent to which, health care professionals delivered opportunistic behaviour change interventions as part of routine practice (Keyworth et al, ). Participants who expressed an interest were invited to supply their contact details, so a member of the research team could arrange a convenient time to conduct the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Behaviour change interventions can be delivered by health care professionals in as few as 30-s (Aveyard et al, 2016;Public Health England, 2016) and are cost-effective (Vijay, Wilson, Suhrcke, Hardeman, & Sutton, 2016). However, health care professionals do not always deliver behaviour change interventions opportunistically during routine patient consultations, even in cases where they perceive patients would benefit from such interventions (Keyworth, Epton, Goldthorpe, Calam, & Armitage, 2018). The barriers and enablers to delivering interventions opportunistically, across specialisms, are currently unclear.…”
Section: Statement Of Contributionmentioning
confidence: 99%
“…No systematic review to date has aimed to collate all of the available evidence in relation to the common barriers and enablers to healthcare professionals delivering behavior change interventions. A recent national survey showed that healthcare professionals deliver behavior change interventions in just 50% of cases where they thought patients would benefit from interventions (Keyworth et al 2018). The specific reasons as to why this is the case, particularly across diverse specialisms, is currently unclear.…”
Section: Introductionmentioning
confidence: 99%